PENGARUH KOMUNIKASI ORGANISASI DALAM MENINGKATKAN MOTIVASI KERJA PEGAWAI DI BADAN PENGELOLA KEUANGAN PENDAPATAN DAN ASET DAERAH KABUPATEN KARO - Refika Maha; Prietsawenny Simamora (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Darma Agung, 2020)
This research study aims at finding out how the influence of Organizational Communication in increasing Work Motivation in the Karo Regency Regional Revenue and Asset Financial Management Agency. The population in this study is all employees at the Karo Regency Regional Revenue and Asset Financial Management Agency which addressed at Jl. Jamin Ginting No. 17 Kabanjahe, Tanah Karo. The research method in this research is a descriptive study with a quantitative approach. From the results of this study it can be concluded that the organizational communication variable partially has a positive and significant effect on employee work motivation in the Regional Revenue and Asset Financial Management Agency Karo District dependent variable (Y). The coefficient of determination (R2) was 82.5%. This means that Work Motivation in the Regional Revenue and Asset Financial Management Agency of Karo Regency is 82.5% while the remaining 17.5% is influenced by other factors outside this study such as leadership variables, work climate, personal ability, work discipline and situation factors, government policies and national economic situation.